2021
DOI: 10.31557/apjcb.2021.6.2.147-153
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Zinc Concentration in Prostate Cancer: Relationship with Prostate Specific Antigen and Gleason Score in a Cohort of Nigerian Men

Abstract: Introduction: Prostate cancer (PCa) is the commonest maliganacy among men of African descent. The possible role of trace elements like Zinc in its aetiogenesis and disease severity remains controversial. This paper aims to identify the relationship between tissue zinc concentration and the occurrence of prostate cancer. And to identify the relationship between the tissue zinc concentration and the disease severity (using the prostate specific antigen (PSA) and Gleason scores (GS)).Methodology: A cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This work showed an increase in levels of PSA in PCa patients when compared to BPH and controls. This result is in agreement with that of Igbokwe et al, 2021 who found an elevation in its level in Nigerian patients.…”
Section: Discussionsupporting
confidence: 93%
“…This work showed an increase in levels of PSA in PCa patients when compared to BPH and controls. This result is in agreement with that of Igbokwe et al, 2021 who found an elevation in its level in Nigerian patients.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, 16 studies were found through backward [ 20 , 24 , 88 98 ] and forward citation searching [ 99 – 101 ], and one study from searching Google Scholar [ 102 ]. Finally, 52 articles were included in this systematic review, of which forty-four were case-controls [ 19 , 21 , 22 , 24 , 57 65 , 67 , 69 – 73 , 75 82 , 84 92 , 94 , 95 , 97 102 ], four were cohorts [ 20 , 26 , 66 , 74 ], and four were analytical cross-sectional studies [ 68 , 83 , 93 , 96 ]. Overall, 50 studies were included in quantitative synthesis and two in qualitative synthesis ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were conducted in the United States [ 19 21 , 24 , 26 , 66 , 72 75 , 80 , 84 ], nine in Nigeria [ 57 , 59 , 68 , 76 – 78 , 83 , 88 , 94 ], five in Turkey [ 58 , 70 , 79 , 85 , 89 ], four in China [ 91 93 , 96 ], three in India [ 61 , 65 , 69 ], two in Saudi Arabia [ 82 , 95 ], two in Russia [ 86 , 87 ], two in Germany [ 62 , 63 ], one study in each other countries, such as Poland [ 60 ], Venezuela [ 90 ], Spain [ 67 ], Sudan [ 99 ], Singapore [ 102 ], Iraq [ 100 ], Serbia [ 97 ], United Kingdom [ 98 ], Iran [ 101 ], Malaysia [ 71 ], Italy [ 64 ], Sweden [ 22 ], and Pakistan [ 81 ]. The follow-up duration of cohort studies ranged from seven to about 28 years [ 20 , 26 , 66 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer is one of the most important causes of cancer mortality among men (Igbokwe et al, 2021). Current treatments have several side effects and researchers are always looking for new therapies with most significant impact on tumor tissue (Anguela and High, 2019).…”
Section: Discussionmentioning
confidence: 99%